Mangrove Conservation - A Survey Based Study on the Awareness and Attitude of General Population of Mumbai - Rushabh Singh,; Aditya Zarapkar,; Aqil Samnani,; Shakti Singh Rathore,; Mayuresh Joshi, (International Journal of Scientific Research in Science and Technology, 2025)
Mumbai’s mangroves are critical coastal ecosystems providing vital services such as shoreline protection and flood mitigation, yet they face increasing threats from rapid urban expansion. The current research work uses a survey-based approach to assess the knowledge, attitudes, and practices of the general population of Mumbai towards mangrove conservation, with a specific focus on the youth demographic (aged 15-25) who comprised over 88% of the participants. The results reveal a significant knowledge deficit among this key demographic. Participants reported a low average self-evaluated knowledge score. A large majority (over 50%) had never visited a mangrove swamp, and many were unaware of their crucial medicinal or economic uses. Furthermore, awareness of the critical ecological functions of mangroves, such as preventing biodiversity loss, mitigating flooding, and combating climate change, was alarmingly low. A concerning 64% of respondents were unaware of local conservation sites, and 71% were not familiar with the Ramsar Site of Mumbai. However, the study also demonstrated that targeted interventions can effectively address this knowledge gap. When provided with a simple infographic, participants' self-evaluated knowledge scores significantly improved from a pre-test average of 5.02 ± 0.158 and a post-test average of 6.91 ± 0.151, proving that accessible educational tools can create a rapid and measurable impact. Building on this finding, the research team further developed a free, user-friendly website as a practical solution to empower citizens with accessible information. This initiative underscores the paper’s central conclusion: that while expert-led efforts are essential, community awareness and individual action are equally crucial for the long-term protection and sustainable management of Mumbai's threatened mangrove ecosystems.
Keywords: Mangroves; Survey; Awareness; Questionnaire